Astronomy of the Milky Way The Observer's Guide to the Southern Sky - Inglis, Mike (The Patrick Moore Practical Astronomy Series,, 2018)
This second edition of Mike Inglis's classic guide to observing the Milky Way in the Southern Hemisphere updates all of the science about the target objects with new findings from the astrophysics field. In addition, the book boasts a larger format with entirely re-drawn maps. Newly laid out for ease of use with an increased number of images in color, it updates and improves the first edition to remain the most comprehensive text on the subject. One of the wonders of the universe we live in is the Milky Way, and this book provides a wonderful tour of its highlights for amateur astronomers observing below the equator. In its pages, Southern Hemisphere observers interested in viewing our own galaxy's finest features will find every constellation that the Milky Way passes through with detailed descriptions of the many objects that can be found therein, including stars, double and multiple stars, emission nebulae, planetary nebulae, dark nebulae and supernovae remnants, open and galactic clusters, and galaxies. The book also details the one thing that is often left out of observing guides - the amazing star clouds of the Milky Way itself. Accompanying the descriptive text there are many star charts and maps, as well as the latest images made by observatories around the world and in space along with those taken by amateur astronomers. This second edition's updated scientific material and an easy-to-use layout perfect for many nights of fruitful observation.